A carbon fiber rail transit brake beam and its preparation method and brake system
By using carbon fiber composite materials to prepare rail transit brake beams, traditional metal brake beams have solved the problems of high weight and high energy consumption, and achieved light weight, high strength and wear resistance, reducing vibration and noise, and extending service life.
Patent Information
- Application Number
- CN202411990635.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
AI Technical Summary
Due to the large weight, high energy consumption and material performance limitations, traditional metal brake beams are difficult to meet the high efficiency, safety, environmental protection and lightweight requirements of modern rail transit systems.
The rail transit brake beam is prepared using carbon fiber composite materials, including chopped carbon fiber and wear-resistant resin. The brake bar and the brake beam body are removed and connected through bolted connections to improve service life.
The lightweight, high-strength, corrosion-resistant and wear-resistant characteristics of the brake beam are achieved, which reduces the frictional vibration between the guide rail and the brake strip, reduces vibration and noise during the braking process of rail vehicles, and extends the service life.
Smart Images

Figure CN119735943A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of locomotive brakes, and in particular relates to a carbon fiber rail transit brake beam and a preparation method and a brake system thereof. Background Art
[0002] As the world's requirements for rail transit systems to be more efficient, safe, environmentally friendly and lightweight continue to increase, traditional metal brake beams can no longer meet the needs of the rapid development of modern rail transit due to their heavy weight, high energy consumption and material performance limitations.
[0003] Unless metal steel has excellent wear resistance, its price is not competitive. In addition, traditional rail transit brake beams are generally made of Q235 or Q420 steel considering the cost. However, when ordinary steel comes into contact with vehicles (such as trains), friction will occur, accompanied by the appearance of sparks, which may cause fire hazards. At the same time, a strong collision sound will be generated, causing trouble to residential areas. At the same time, due to its poor wear resistance, it will rust during long-term use, greatly reducing its service life.
[0004] Carbon fiber materials, with their light weight, high strength, corrosion resistance, fatigue resistance and excellent thermal expansion coefficient, have gradually become an important direction for material innovation in the field of rail transit. Summary of the invention
[0005] The present invention proposes a carbon fiber rail transit brake beam, a preparation method thereof and a brake system. The present invention uses a carbon fiber composite material prepared from chopped carbon fiber and wear-resistant resin as the material of the rail transit brake beam. The carbon fiber composite material has the characteristics of light weight, high strength, corrosion resistance and high wear resistance, which improves the stability and durability of its long-term performance while reducing the weight; and has better impact resistance, can reduce the friction vibration between the guide rail and the brake strip, and reduce the vibration and noise during the braking process of the rail vehicle.
[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solution: A carbon fiber rail transit brake beam comprises a brake beam body and a brake strip;
[0007] The brake strip is detachably arranged on the brake beam body; the brake strip and the brake beam body are detachably connected by bolt connection. In this combination, if either of them is damaged, the damaged parts can be disassembled and replaced, which effectively increases the service life of the brake beam;
[0008] The brake beam body and the brake strip are both made of carbon fiber composite materials;
[0009] The carbon fiber composite material comprises chopped carbon fibers and wear-resistant resin.
[0010] Among many lightweight materials, carbon fiber materials have excellent comprehensive mechanical properties: high specific strength, specific modulus and specific energy absorption (energy absorbed per unit mass within the effective destruction length). Under the design principle of equal stiffness or equal strength, carbon fiber material structures are more than 50% lighter than low-carbon steel structures and 30% lighter than magnesium / aluminum alloy structures.
[0011] In the present invention, the carbon fiber composite material itself can effectively improve the impact resistance due to the toughness of the wear-resistant resin and the energy absorption effect of the interface between the fiber and the resin matrix. It is applied to the preparation of brake beams and can effectively reduce vibration and noise during braking.
[0012] Carbon fiber composites also have high strength and stiffness. Carbon fiber is more than five times stronger than steel, and its lightweight and high-strength properties allow the composite to maintain good stability when subjected to large stresses and strains. In addition, carbon fiber composites also have high stiffness, good bending and torsion resistance, and good fatigue properties. Under cyclic loads, carbon fiber composites can maintain a high load-bearing capacity and are not prone to fatigue damage, allowing the prepared brake beam to be repeatedly impacted without damage.
[0013] In addition, carbon fiber composite materials also have excellent corrosion resistance and radiation resistance. Since the matrix resin in carbon fiber has good corrosion resistance, it is not easily affected by chemical corrosion and the environment during use, thus ensuring its long-term performance stability and durability, and ensuring the service life of the brake beam in the harsh environment of rail transportation.
[0014] Preferably, the wear-resistant resin is a silicone-modified polyurethane resin; polyurethane has high mechanical strength and oxidation stability; has high flexibility and resilience; has excellent oil resistance, solvent resistance, water resistance and fire resistance, and effectively reduces the risk of friction fire; silicone-modified polyurethane resin is generally better in heat resistance than ordinary polyurethane resin; the introduction of silicone further improves the thermal stability of the material, so that it can maintain its performance at higher temperatures; silicone-modified polyurethane resin has better weather resistance, can resist the erosion of natural factors such as ultraviolet rays, oxidation and aging, and can still maintain good performance under long-term use;
[0015] The brake beam body comprises, by weight: 15-20 parts of organosilicon-modified polyurethane resin, 20-40 parts of chopped carbon fiber, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant and 0.1-0.5 parts of defoamer;
[0016] The brake strip comprises, in parts by weight: 30-50 parts of organosilicon-modified polyurethane resin, 40-60 parts of chopped carbon fiber, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant, 0.1-0.5 parts of defoaming agent, 5-15 parts of thixotropic agent and 5-10 parts of flame retardant.
[0017] The brake beam body does not come into contact with the rails, so the formulation does not contain thixotropic agents and flame retardants. The brake strip is in direct contact with the wheel, requiring higher strength and hardness to ensure wear resistance. Therefore, the content of silicone-modified polyurethane resin is higher than that of the brake beam body.
[0018] The plasticizer is a substance used to increase the flexibility, plasticity and fluidity of the material. For products with higher requirements for strength and hardness, the amount of plasticizer used is less, so the plasticizer content in the brake strip is lower than the plasticizer content in the brake beam body.
[0019] Preferably, the chopped carbon fiber is PAN-based chopped carbon fiber. PAN-based chopped carbon fiber has the characteristics of light weight, high strength, high modulus, and wear resistance, which makes the carbon fiber chopped strands perform well in occasions where they need to withstand harsh working conditions such as wear, friction, and high temperature, and withstand greater mechanical stress and wear.
[0020] Preferably, the catalyst is an alcohol compound catalyst, such as triethanolamine, DMEA, etc. Such catalysts have high catalytic efficiency, environmental protection (low pollution, environmentally friendly), economy, improved product performance (such as hardness, wear resistance, chemical corrosion resistance, etc.), and production controllability (control of the reaction kinetics, improved product purity and performance).
[0021] Preferably, the coupling agent is a silane coupling agent or a titanate coupling agent, which can be used to improve the interfacial bonding performance between carbon fiber and polyurethane, and can also bridge the carbon fiber and polyurethane together through a chemical reaction, thereby improving the interfacial bonding strength between the two.
[0022] Preferably, the plasticizer is dioctyl terephthalate (DOTP), which has good electrical properties and cold resistance, low volatility, high plasticizing efficiency, and can be used for products with high insulation, extraction resistance, heat resistance and good softness, and is suitable as a plasticizer for polyurethane; this type of plasticizer can improve the wear resistance of polyurethane resin to a certain extent, while maintaining good flexibility and processing performance;
[0023] The thickener is an acrylic emulsion;
[0024] The stabilizer is a phenolic heat stabilizer;
[0025] The dispersant is a polyester dispersant;
[0026] The defoaming agent is a polyether modified silicon defoaming agent.
[0027] Preferably, the flame retardant of the present invention is a solid flame retardant, such as antimony trioxide, aluminum hydroxide, etc. Flame retardants are generally divided into phosphorus-containing flame retardants, halogen-containing flame retardants, and solid flame retardants. Phosphorus-containing flame retardants may produce a certain amount of smoke and toxic gases when burning, causing certain harm to human health and the environment; phosphorus-containing flame retardants usually have a certain degree of degradability, which may affect the performance and service life of the material after long-term use; the production cost of phosphorus-containing flame retardants is relatively high, which will increase the production cost of the material. Halogen-containing flame retardants Halogen-containing flame retardants will produce a large amount of toxic gases and smoke when burning, causing serious harm to human health and the environment; the production and use of halogen-containing flame retardants may cause certain pollution to the environment; the production and use of halogen-containing flame retardants may cause safety hazards such as fire. Solid curing agents have good thermal stability and can maintain stable performance at high temperatures.
[0028] Preferably, the thixotropic agent is fumed silica. Fumed silica: also known as fumed white carbon black, is a commonly used thixotropic agent. It has a spherical structure, an average original particle size of 7 to 40 nm, a large specific surface area, and can absorb more water, so it often needs to be dried before use. Fumed silica can also be treated with silane compounds or organic isocyanates to make it hydrophobic. It is a commonly used thixotropic agent in polyurethane sealants, but it will only show thixotropy when added in sufficient amounts. Due to the high fluidity and small size effect of fumed silica, the surface of the material becomes denser and finer, and the friction coefficient becomes smaller. In addition, the high strength of the nanoparticles greatly enhances the wear resistance of the material. Therefore, fumed silica is selected as a thixotropic agent in brake strips.
[0029] The present invention also discloses a method for preparing the above-mentioned carbon fiber rail transit brake beam, which is characterized by comprising the following steps:
[0030] S1. Proportion
[0031] The components of the brake beam body are mixed in proportions by weight: 15-20 parts of organosilicon-modified polyurethane resin, 20-40 parts of chopped carbon fiber, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant and 0.1-0.5 parts of defoamer;
[0032] The components of the brake strip are mixed in proportions by weight: 30-50 parts of organosilicon-modified polyurethane resin, 40-60 parts of chopped carbon fiber, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant, 0.1-0.5 parts of defoamer, 5-15 parts of thixotropic agent and 5-10 parts of flame retardant;
[0033] S2, compression molding
[0034] The brake beam body and the brake strip are mixed according to the proportions in step S1, and then molded and cured;
[0035] The pressure is 100t, the curing temperature is 110-150℃, and the curing time is 30min-1h.
[0036] The present invention also discloses a carbon fiber rail transit brake system, comprising the carbon fiber rail transit brake beam and a track, wherein two carbon fiber rail transit brake beams are arranged on both sides of the track;
[0037] The carbon fiber rail transit brake beam is arranged parallel to the track, and can reciprocate relative to the track in a direction perpendicular to the track, so that the gap between the two carbon fiber rail transit brake beams matches the wheel width of the rail vehicle, and the two carbon fiber rail transit brake beams are used to squeeze the wheel to achieve the effect of friction deceleration.
[0038] Compared with the prior art, the beneficial effects of the present invention are: the present invention selects short-cut carbon fiber materials, and then cooperates with wear-resistant resin, so as to ensure the impact resistance and wear resistance of the brake beam, realize the high performance and lightness of the brake beam, and effectively reduce noise.
[0039] The brake beam of the present invention is applied to tracks of high-speed trains, subways, light rails, etc., for auxiliary braking of vehicles, which reduces the wear on the brake components of the rail vehicle itself, can effectively improve the braking efficiency, enhance the structural strength and reduce the maintenance cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a schematic diagram of the structure of the carbon fiber rail transit brake beam of the present invention;
[0041] Figure 2 It is a structural schematic diagram of the carbon fiber rail transit braking system of the present invention;
[0042] Figure 3 It is the first-order modal diagram of the carbon fiber rail transit brake beam in the present invention;
[0043] Figure 4 It is the second-order modal diagram of the carbon fiber rail transit brake beam in the present invention;
[0044] Figure 5 It is the third-order modal diagram of the carbon fiber rail transit brake beam in the present invention;
[0045] In the figure, 1 is a brake beam body, 2 is a brake strip, and 3 is a track. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings.
[0047] like Figure 1 As shown, the carbon fiber rail transit brake beam of the present invention includes a brake beam body 1 and a brake strip 2.
[0048] The brake strip 2 is detachably arranged on the brake beam body 1, and the brake beam body 1 and the brake strip 2 are fastened with bolts through bolt holes. The brake strip 2 is pre-embedded with a threaded steel sleeve during production to facilitate subsequent connection and fixation with the brake beam body 1. The brake beam body 1 is provided with a bolt connection hole.
[0049] Different numbers of reinforcing ribs are arranged on the upper and lower sides of the brake beam body 1 so that it has sufficient supporting strength to ensure the stability of the brake strip 2 .
[0050] The brake beam body 1 and the brake strip 2 are both made of carbon fiber composite materials.
[0051] The carbon fiber composite material comprises chopped carbon fibers and wear-resistant resin.
[0052] Carbon fiber materials have good toughness, good impact resistance and energy absorption capacity, which can improve the collision energy absorption capacity of the car body and structural parts. They also have high damping, good shock resistance and significant noise reduction effect. Although the weight of carbon fiber materials is about 50% lighter than steel and about 30% lighter than magnesium / aluminum alloys, their collision energy absorption capacity is 6 to 7 times that of steel and 3 to 4 times that of aluminum, which greatly improves the collision safety of the material. Carbon fiber materials have a large vibration reduction coefficient and strong vibration absorption capacity, so they can be used in transmission systems and engine components. This not only reduces the weight, but also reduces vibration and noise, thereby improving comfort and greatly satisfying the usability of the product.
[0053] The brake beam body 1 comprises, by weight: 15-20 parts of silicone modified polyurethane resin, 20-40 parts of chopped carbon fibers, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant and 0.1-0.5 parts of defoaming agent.
[0054] The brake strip 2 includes, by weight: 30-50 parts of silicone modified polyurethane resin, 40-60 parts of chopped carbon fiber, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant, 0.1-0.5 parts of defoaming agent, 5-15 parts of thixotropic agent and 5-10 parts of flame retardant.
[0055] Specifically, the resin in the brake beam body is silicone-modified polyurethane resin. The chopped carbon fiber is PAN-based chopped carbon fiber. The catalyst is an alcohol compound catalyst. The coupling agent is a silane coupling agent. The plasticizer is dioctyl terephthalate (DOTP). The thickener is an acrylic emulsion. The stabilizer is a phenolic heat stabilizer. The dispersant is a polyester dispersant. The defoamer is a polyether-modified silicon defoamer. The thixotropic agent is fumed silica. The flame retardant is a melamine flame retardant.
[0056] The method for preparing the carbon fiber rail transit brake beam of the present invention comprises the following steps:
[0057] S1. Proportion
[0058] The components of the brake beam body 1 are mixed in proportions by weight: 15-20 parts of silicone modified polyurethane resin, 20-40 parts of chopped carbon fibers, 0.1-1 parts of catalysts, 0.1-2 parts of coupling agents, 5-10 parts of plasticizers, 2-5 parts of thickeners, 0.5-2 parts of stabilizers, 0.1-1 parts of dispersants and 0.1-0.5 parts of defoaming agents.
[0059] The components of the brake strip 2 are mixed in proportions by weight: 30-50 parts of silicone modified polyurethane resin, 40-60 parts of chopped carbon fiber, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant, 0.1-0.5 parts of defoaming agent, 5-15 parts of thixotropic agent and 5-10 parts of flame retardant.
[0060] S2, compression molding
[0061] The brake beam body 1 and the brake strip 2 are mixed according to the proportions in step S1 and then molded and cured.
[0062] The pressure is 100t, the curing temperature is 110-150℃, and the curing time is 30min-1h.
[0063] like Figure 2 As shown, the carbon fiber rail transit brake beam of the present invention is used in a carbon fiber rail transit brake system, and two of the carbon fiber rail transit brake beams are arranged oppositely on both sides of a track 3, and the track 3 is fixedly arranged on the ground.
[0064] The carbon fiber rail transit brake beam is arranged parallel to the track 3, that is, the brake strip 2 is arranged parallel to the side of the wheel, and can reciprocate relative to the track 3 in a direction perpendicular to the track 3. Figure 2 As described, when the train enters, pneumatic or hydraulic pressure is used to push the brake beams on both sides of the track closer to the train track, so that the brake strips on both sides of the track contact the side of the train wheel, achieving the effect of clamping and deceleration. The hydraulic rods are distributed at intervals along the axial direction of the carbon fiber rail transit brake beam. The hydraulic rod is fixed relative to the track 3 (not shown in the figure), and the telescopic rod of the hydraulic rod is connected to the brake beam body 1, and all the hydraulic rods are uniformly controlled, so that the carbon fiber rail transit brake beam moves parallel to the track 3.
[0065] The brake beam of the present invention includes a brake beam body and a brake strip, both of which are made of polyurethane resin and carbon fiber during production. However, since the brake beam body does not contact and rub against the rails, the thixotropic agent and the flame retardant are removed from the proportion, and the content of the organic modified polyurethane is low. Therefore, the influence of the components on the performance of the brake strip 2 is mainly considered in this embodiment.
[0066] Table 1 Brake strips with different ratios of silicone-modified polyurethane resin and carbon fiber
[0067]
[0068]
[0069] Note: Proportioning is based on weight.
[0070] In Examples 1-5, the catalyst, coupling agent, plasticizer, thickener, stabilizer, dispersant, defoamer, thixotropic agent, and flame retardant are used as quantitative amounts, and the polyurethane resin and carbon fiber are used as variable amounts.
[0071] According to the standard track of 1435mm, the wheel diameter is 838mm, and the normal running speed of ordinary trains is 60-120km / h. The wheel speed is 380r / min-760r / min, and the speed is below 380r / min or below 760r / min when braking.
[0072] The comparison of friction coefficient and wear rate of different resin content and carbon fiber content is shown in Table 2:
[0073] Table 2 Friction coefficient and wear rate of different resin content and carbon fiber content
[0074]
[0075] By comparison, it can be seen that with the increase of resin content and the decrease of carbon fiber content, the friction coefficient and wear rate are generally reduced; but when the resin content is 40 parts and the fiber content is 50 parts, the wear rate is the smallest.
[0076] Furthermore, the friction coefficient and wear rate can be compared by changing the content of thixotropic agent:
[0077] Table 3 Brake strips with different contents of thixotropic agent
[0078] Example 6 Example 7 Resin 40 40 fiber 50 50 catalyst 0.5 0.5 Coupling agent 1 1 Plasticizers 8 8 Thickener 5 5 Stabilizer 1 1 Dispersants 0.5 0.5 Defoaming agent 0.3 0.3 Thixotropic agent 5 15 Flame retardants 8 8
[0079] Note: Proportioning is based on weight.
[0080] Table 4 Friction coefficient and wear rate of different thixotropic agent contents
[0081]
[0082]
[0083] As shown in Table 3 and Table 4, by comparison, it can be seen that the increase in the thixotropic agent content reduces the friction coefficient and wear rate of the brake strip.
[0084] Studies have pointed out that the noise generated by the braking system during train operation contributes the most. "Railway Boundary Noise Limits and Measurement Methods" GB12525-90 stipulates that the boundary railway noise limit for existing railways is 70dB (A) during the day and at night, and the boundary railway noise limit for newly built railways is 70dB (A) during the day and 70dB (A) at night. By comparing the brake beam body and brake strips made by the present invention with the brake beam brake strips made of steel, the noise values measured by the near-sound field measurement method are as follows:
[0085] Table 5 Noise value comparison
[0086] Noise value dB(A) Carbon fiber composite material of the present invention 52 Steel 86
[0087] Through the above comparison, it can be concluded that the brake strip in the carbon fiber rail transit brake beam of the present application effectively reduces noise.
[0088] In addition, after the modal analysis of the carbon fiber brake beam and the steel (45 steel) brake beam, the first-order mode of the carbon fiber brake beam (such as Figure 3 ), 2nd order mode (such as Figure 4 ), 3rd order mode (such as Figure 5) values are 192.59HZ, 204.07HZ, 209.32HZ respectively, and the 1st, 2nd and 3rd modal values of the steel brake beam are 372.34HZ, 372.46HZ and 380.67HZ respectively. By comparison, it can be seen that the carbon fiber rail transit brake beam of the present invention has a lower natural frequency, which will make the frequency range of vibration attenuation wider, the attenuation is enhanced, and the vibration is smaller. Therefore, in the present invention, the carbon fiber composite material of the carbon fiber rail transit brake beam reduces the vibration between the guide rail and the brake beam and reduces the noise.
[0089] The performance of the brake beam body and the brake strip prepared by the present invention was tested, and the test data are shown in Table 6:
[0090] Table 6 Related test data indicators
[0091] name Tensile strength(MPa) Elastic modulus(GPa) Bending strength(MPa) Brake beam body 685 62 710 Brake strips 732 74 795
[0092] Table 7 Performance indicators of existing steel
[0093] Tensile strength(MPa) Yield strength (MPa) Q235 370-500 235 Q420 520-670 420-400 Q460 550-710 440-460
[0094] After testing the performance of the brake beam body and brake strip prepared by the present invention and comparing them with the performance indicators of existing steel materials, it was found that the brake beam body and brake strip prepared by the present invention have excellent tensile strength and bending strength and better impact resistance.
Claims
1. A carbon fiber rail transit brake beam, characterized in that: It comprises a brake beam body (1) and a brake strip (2); The brake strip (2) is detachably arranged on the brake beam body (1); The brake beam body (1) and the brake strip (2) are both made of carbon fiber composite materials; The carbon fiber composite material comprises chopped carbon fibers and wear-resistant resin.
2. The carbon fiber rail transit brake beam according to claim 1, characterized in that: The wear-resistant resin is a silicone-modified polyurethane resin; The brake beam body (1) comprises, in parts by weight: 15-20 parts of organosilicon-modified polyurethane resin, 20-40 parts of chopped carbon fibers, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant and 0.1-0.5 parts of defoamer; The brake strip (2) comprises, in parts by weight: 30-50 parts of organosilicon-modified polyurethane resin, 40-60 parts of chopped carbon fibers, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant, 0.1-0.5 parts of defoamer, 5-15 parts of thixotropic agent and 5-10 parts of flame retardant.
3. The carbon fiber rail transit brake beam according to claim 2, characterized in that: The chopped carbon fibers are PAN-based chopped carbon fibers.
4. The carbon fiber rail transit brake beam according to claim 2, characterized in that: The catalyst is an alcohol compound catalyst.
5. The carbon fiber rail transit brake beam according to claim 2, characterized in that: The coupling agent is a silane coupling agent or a titanate coupling agent.
6. The carbon fiber rail transit brake beam according to claim 2, characterized in that: The plasticizer is dioctyl terephthalate (DOTP); The thickener is an acrylic emulsion; The stabilizer is a phenolic heat stabilizer; The dispersant is a polyester dispersant; The defoaming agent is a polyether modified silicon defoaming agent.
7. The carbon fiber rail transit brake beam according to claim 2, characterized in that: The flame retardant is a solid flame retardant.
8. The carbon fiber rail transit brake beam according to claim 2, characterized in that: The thixotropic agent is fumed silica.
9. A method for preparing a carbon fiber rail transit brake beam according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Proportion The components of the brake beam body (1) are mixed in proportions by weight: 15-20 parts of organosilicon-modified polyurethane resin, 20-40 parts of chopped carbon fibers, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant and 0.1-0.5 parts of defoamer; The components of the brake strip (2) are mixed in proportions by weight: 30-50 parts of organosilicon-modified polyurethane resin, 40-60 parts of chopped carbon fibers, 0.1-1 parts of catalyst, 0.1-2 parts of coupling agent, 5-10 parts of plasticizer, 2-5 parts of thickener, 0.5-2 parts of stabilizer, 0.1-1 parts of dispersant, 0.1-0.5 parts of defoamer, 5-15 parts of thixotropic agent and 5-10 parts of flame retardant; S2, compression molding The brake beam body (1) and the brake strip (2) are mixed according to the proportions in step S1, and then molded and cured; The pressure is 100t, the curing temperature is 110-150℃, and the curing time is 30min-1h.
10. A carbon fiber rail transit brake system, comprising the carbon fiber rail transit brake beam according to any one of claims 1 to 8, characterized in that: It also includes a track (3), wherein the two carbon fiber rail transit brake beams are arranged oppositely on both sides of the track (3); The carbon fiber rail transit brake beam is arranged parallel to the track (3) and can reciprocate relative to the track (3) in a direction perpendicular to the track (3).